2022
DOI: 10.1177/01461672211068910
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life and Coping With Everyday Stressors

Abstract: Meaning in life (MIL) has been proposed to improve coping and resilience. Yet MIL’s association with coping has primarily been investigated in the context of extreme stressors and trauma, often using varied measures of MIL. Is MIL associated with varied coping strategies, coping self-efficacy, and distress in relation to commonly experienced, everyday challenges? Using diverse methodological designs, five studies (total N = 1,646) investigated the association between MIL and coping strategies/appraisals pertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…A second protective factor that has been consistently linked with psychological resilience and shows strong connections to media entertainment is the presence of meaning in life (Pangallo et al, 2015). Higher levels of meaning in life have been identified as a central protective factor and linked to mental health and positive adjustment to various forms of adversity or traumatic events (Park, 2017;Ward et al, 2022). Furthermore, meaning making, that is, restoring meaning after trauma and critical life events, is an important mechanism that strengthens resilience (Park, 2017), for example through the acceptance of change or the reappraisal of the situation as an opportunity for growth or a source of wisdom (Folkman and Moskowitz, 2007).…”
Section: The Present Studymentioning
confidence: 99%
“…A second protective factor that has been consistently linked with psychological resilience and shows strong connections to media entertainment is the presence of meaning in life (Pangallo et al, 2015). Higher levels of meaning in life have been identified as a central protective factor and linked to mental health and positive adjustment to various forms of adversity or traumatic events (Park, 2017;Ward et al, 2022). Furthermore, meaning making, that is, restoring meaning after trauma and critical life events, is an important mechanism that strengthens resilience (Park, 2017), for example through the acceptance of change or the reappraisal of the situation as an opportunity for growth or a source of wisdom (Folkman and Moskowitz, 2007).…”
Section: The Present Studymentioning
confidence: 99%
“…In experimental studies, researchers have observed condition differences in meaning in life ratings-even on broad trait measures of meaning in life-following an array of laboratory manipulations inducing qualities including social belonging (Lambert et al, 2013), nostalgia (Sedikides et al, 2018), or repeating patterns (Heintzelman et al, 2013). Furthermore, across daily diary studies including once daily meaning in life measures, there is consistent and substantial within-person variance in meaning in life, for example, daily diary studies have produced the following within-person variance estimates: 54% (Machell et al, 2015a), 44% (Ward et al, 2022), and31% (Jayawickreme et al, 2021).…”
Section: Capturing Variations In Meaning In Life Within Personmentioning
confidence: 99%
“…Daily diary methods have been used more frequently than the ESM in meaning in life research to further understand whose lives are meaningful (Dolan et al, 2017), the stability of meaning in life across time (Steger & Kashdan, 2013), and the relation between daily search for meaning & presence of meaning in life (Morse et al, 2021;Newman & Nezlek, 2019). Daily diary methods have demonstrated relationships between daily reports of meaning in life and daily reports of psychological constructs including psychological well-being (Hadden & Smith, 2019), curiosity (Kashdan & Steger, 2007), and gratitude (Nezlek et al, 2017), behaviors including the use of coping strategies (Ward et al, 2022), and experiences such as daily social and achievement events (Machell et al, 2015b).…”
Section: Building On Daily Diary Studies Of Meaning In Lifementioning
confidence: 99%
“…Existentialism theory suggests that the presence of meaning is a protective factor against depression (Mascaro & Rosen, 2008), which is consistent with the cognitive theory of depression (Beck, 1987). Higher levels of presence of meaning lead individuals to live purpose‐filled lives and ensure they have more resources to cope with stressful events (Sedikides et al, 2018; Ward et al, 2023); therefore, they are at a lower risk of depression than those with lower levels of presence of meaning (Disabato et al, 2017). Chen et al (2021) found that presence of meaning mediates the relationship between the search for meaning and depression; that is, the process by which people search for meaning facilitates higher levels of the presence of meaning, which in turn reduces depression.…”
Section: Introductionmentioning
confidence: 99%